Leek (Allium fistulosum, L.) Growth and Yield as Affected by Cow Manure and Guava Waste Liquid Organic Fertilizer - Nanik Setyowati; Nova Hardianto; Widodo Widodo; Zainal Muktamar (Agro Bali : Agricultural Journal, 2021)
Fruit waste can be a good source of liquid organic fertilizer (LOF) because it contains macro and micronutrients needed by plants. This study aims to determine the type and concentration of LOF for the growth and yield of leek (Allium fistulosum, L.). This research was conducted from June to August 2019, in Pematang Gubernur, Muara Bangkahulu, Bengkulu City, Indonesia. Treatment consist of types of Liquid Organic Fertilizer (LOF) which were cow manure (CM) and guava waste (GW) at concentrations of 25%, 50%, and 75%. Experimental treatment included; without LOF, CM LOF (25%), CM LOF (50%), CM LOF (75%), GW LOF (25%), GW LOF (50%), GW LOF (75%), CM LOF + GW LOF (25%), CM LOF + GW LOF (50%) and CM LOF + GW LOF (75%). The study used a completely randomized design (CRD), one factor, repeated five times. Differences in LOF concentration and source significantly affected the number of leaves and tiller diameter. Nonetheless, it did not affect the number of tillers, plant height, and fresh weight. Cow manure liquid organic fertilizer at a 50 % concentration raised the number of leaves by 35 %, whereas guava waste increased the leaves numbers by 25%. With the application of guava waste liquid organic fertilizer at a concentration of 75%, so the number of tillers increased by 23%.